Lower thermal tolerance restricts vertical distributions for juvenile albacore tuna (Thunnus alalunga) in the northern limit of their habitats - Matsubara, Naoto; Aoki, Yoshinori; Aoki, Akiko; Kiyofuji, Hidetada (Frontiers in Marine Science, 2024)
Introduction Evaluating the thermal tolerance of commercially valuable tuna species and their behavioral responses to the limits of this tolerance is essential for evaluating the effects of changes in water temperature driven by global climate change on their distribution and fisheries. We aimed to identify the lower thermal tolerance (Tmin) of juvenile albacore tuna (ALB) and evaluate their behavioral response to Tmin by focusing on wild behavior in the northern distributional limit. Additionally, we investigated how vertical behavior is linked to the vulnerability of ALB to Japanese longline (LL) and pole-and-line (PL) fisheries. Methods We explored the swimming depths and water temperatures of four previously reported tagged individuals migrating from subtropical to temperate areas and identified Tmin and its depths in the water column as unfavorable depths (DTmin). To investigate the spatial patterns of ALB fishery grounds for LL and PL fisheries, we analyzed hotspots specific to each type of gear using the historical Japanese fishery logbook for both fisheries. Results Comparisons of the fishery grounds between the two fisheries revealed that PL hotspots appeared in the northern areas, while LL hotspots were in the southern regions. We also discovered that the vertical distribution of ALB became shallow in high-latitude areas, which were strongly affected by DTmin shallowing at high latitudes. Discussion These results provide evidence of a behavioral response among juvenile ALB that avoids Tmin by remaining at the surface. We discuss the implications of the results for latitudinal changes in the vulnerability of ALB to fisheries in terms of the overlapping depth between ALB vertical habitats and the gear-setting depth for each fishery.